Alternatif Pemberian Makanan Tambahan (PMT) Bahan Pangan Lokal pada Balita Stunting di Desa Karunia - Kariani, Ni Ketut; Aboka, Helmi; Abadi, Siti Rafika; Lanyumba, Hajjaria I; Kurniawan, Adi; Pasau, Febri Yolanda; Tarakolo, Hernitis Silvana; Ahlan, Mauzatul Hasanah; Natasya, Putri Wilda; Suspia, Suspia; Pratiwi, Vira; Pramono, Wiandi Nur Annisa Ms. (Civiliza Publishing, 2024)
The percentage of Stunting in Indonesia according to the 2018 Basic Health Study was 30.8%. In that year, the stunting population was higher than other cases of infant nutrition (3.9%), malnutrition (3.8%), thin nutrition (10.2%) and obesity (8%). Then based on the results of the 2021 Indonesian Nutrition Status Survey (SSGI) showed that the prevalence rate of stunting in Indonesia in 2021 reached 24.4%. The prevalence of nutritional status of toddlers in Central Sulawesi Province with Underweight problems was 11.1% of the national target of 14%, stunting was 12.9% of the national target of 18.4%, undernourished toddlers were 5.0% of the RPJMD target of 10% and toddlers with severe malnutrition were 0.8% of the RPJMD target of 1%. To provide mothers with an understanding of stunting through the provision of stunting education using leaflets and the provision of local food MPASI for stunted children. Implementation of community service activities in Karunia Village consisted of education about stunting using leaflets face-to-face and providing MPASI local food ingredients for 2 weeks to stunted children. Pre-test results of weight and height of stunted toddlers in Karunia Village, the highest weight was 13.3 kg, and the lowest weight was 4.5 kg. While for the highest height was 93.9 cm, and the lowest height was 52.1 cm. Post-test weight and height of stunted toddlers in Karunia Village, the highest weight was 13.7 kg, and the lowest weight was 8.9 kg. While for the highest height was 93.9 cm, and the lowest height was 79 cm. In general, the implementation of community service activities was successful because the activities were carried out according to target. The output of the activity has been achieved, namely an increase in mothers' knowledge about the symptoms of stunting as an effort to prevent stunting in mothers who have stunted children.